Evaluation of the economic feasibility of water harvesting for irrigation in a large semi-arid tropical catchment in northern Australia. (February 2016) - Petheram, C.; McKellar, L.; Holz, L.; Poulton, P.; Podger, S.; Yeates, S.
Abstract: There is interest by governments and private organisations in exploring alternative models of irrigation in parts of northern Australia where there has been little irrigation development to date. One alternative is 'water harvesting', which is defined here as the practice of pumping or diverting water during streamflow events and either applying directly to a crop or (more commonly) holding water in off-stream storage on a property for later use. This study presents a detailed farm-scale bio-economic analysis of water harvesting using river system modelling to represent the interactions between farm-scale returns, reliability of extraction and scale of development. In doing so the farm-scale viability of irrigation within a whole of catchment is assessed, and uses the Flinders catchment, a large, semi-arid tropical catchment in northern Australia as a case study. Extraction reliability varied spatially across the catchment and decreased with increasing total catchment extraction. The farm-scale profitability of water harvesting enterprises was found to be particularly sensitive to fluctuations in price, reliability of water extraction, discount rate, cost of storage and timing of crop-failure years. For crops requiring off-site processing, the existence of local processing facilities was a major factor. This study also highlighted that for irrigation developments based on water harvesting there is potential for serious mismatches between the timing of streamflow and time at which planting must occur. For the cropping scenarios modelled here for the Flinders catchment it was found that mosaics of irrigation based on water harvesting and off-stream storage are unlikely to be profitable, and short to medium season crops provided the best return, although still negative. This is because land developed for irrigation of short to medium season crops returns no income for six or more months every year, while for permanent cropping the cost of constructing a storage that could provide water for irrigation throughout the year is prohibitively expensive. Assuming an optimal water storage to pump capacity ratio of 5, it was found that if an additional 240 GL of water were added to the existing 105 GL catchment entitlement, most new irrigators could extract their entitlement in approximately 70 to 80% of years, discounting any environmental or legislative issues that would need to be addressed. At these reliabilities, most high value crops would require high prices to be sustained through the entire investment period (for which there is no historical precedent), to acquire a return equal to inflation. The method and results presented in this manuscript would be useful to water planners and regulators to help inform water allocation, pricing decisions and policy initiatives, particularly where agricultural development may be based on water harvesting. Highlights: A method for assessing the profitability of water harvesting is presented. The sensitivity of profitability to different factors was examined. The reliability of water extraction was shown to be an important consideration. For water harvesting matching the timing of streamflow and sowing can be crucial. In the Flinders catchment water harvesting is unlikely to be profitable.